WACANA BENTURAN PERADABAN DALAM NOVEL THE SATANIC VERSES KARYA SALMAN RUSHDIE - Ali, Moch. (Diksi, 2008)
This article is about a research describing a discourse on the clash ofcivilizations represented in the person of Mahoud, the Hellenized Islamic prophetin the pejorative novel of the Western World The Satanic Verses by SalmanRushdie, who was born in the Bhí£rat tradition of India. As a famous novel in thatworld, The Satanic Verses politically represents a hegemony in discourse of asecretive quantum literary industry to create a clash in civilization between theEast and the West through a deconstuction of religious power.The research employs a descriptive qualitative technique in the dataanalysis, which is textually done by understanding (1) the position of SalmanRushdie as a Indian-English author toward the well-known Islamic religioussymbols in creating the representation and (2) his way in representing Mahoud theprophet in the novel.The research uses Stuart Hall's and Michel Foucault's theory ofrepresentation. As a result, the analysis shows that The Satanic Verses as a novel byan author of Indian and English blood offers a literary discourse as an imaginativepolitical manisfesto through the projection of language power. Obviously, theimaginative discourse also shows how the Indian-English author has an absolutecontrol over the literary language play used in the representation of religioussymbols.Keywords: Bhí£rat, the West, Islam, Indian-English author, The Satanic Verses